2020
DOI: 10.1364/oe.394971
|View full text |Cite
|
Sign up to set email alerts
|

Robust neural network receiver for multiple-eigenvalue modulated nonlinear frequency division multiplexing system

Abstract: Nonlinear frequency division multiplexing (NFDM) has been shown to be promising in overcoming the fiber Kerr nonlinearity limit. In multiple-eigenvalue modulated NFDM systems, the transmission capacity increases with the number of modulated eigenvalues. However, as the number of modulated eigenvalues increases, the complexities of the signal waveform and the nonlinear Fourier transform (NFT) algorithm for demodulation increase dramatically as well, while the accuracy drops significantly. Meanwhile, impairments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Finally, we note that the problem of recovering a few solitons from a given pulse utilizing NN has been studied in 31,43,44,67 . However, the NN architectures used in these works are much more simple as far as we need to identify and denoise just several solitonic parameters, while in our work we recovered 1024 complex numbers representing the continuous NF spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we note that the problem of recovering a few solitons from a given pulse utilizing NN has been studied in 31,43,44,67 . However, the NN architectures used in these works are much more simple as far as we need to identify and denoise just several solitonic parameters, while in our work we recovered 1024 complex numbers representing the continuous NF spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…In the other approach, the NFT operation at the receiver is entirely replaced by the NN element. It has been shown that this approach, indeed, results in a considerable improvement of the NFT-based transmission system functioning 31,43,44 . But, despite the benefits rendered by such a NN utilisation, the NNs emulating the NFT operation have so far been mostly used in the NFDM systems operating with solitons only, and the NN structure used there was relatively simple.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…To facilitate improvement in the received power margin, use of an additional decision process based on the Euclidian minimum distance (MD) has been demonstrated [16]. In addition, machine learning-based demodulation methods for eigenvalue modulation, such as classification [17]- [20] and equalization [21], [22], have been investigated in recent years. Demodulation methods based on time-domain (TD) artificial neural networks (ANNs) for quadrature phase shift keying (QPSK) modulation of spectral amplitudes with two eigenvalues and on-off encoding of four-eigenvalue modulation have been proposed [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Since neural networks have gained increased interest for optical communication systems [25,26], they are also a promising candidate for equalizing NFT-based communication [27,28]. Eigenvalue communication systems, where the receiver is based on a neural network only, have been proposed in [29,30], which is a very effective alternative to the standard NFT approach.…”
Section: Introductionmentioning
confidence: 99%